KEPEMIMPINAN KEPALA KANTOR DALAM MENINGKATKAN KINERJA PEGAWAI PADA UPTD BALAI TEKKOMDIK DINAS PENDIDIKAN ACEH - Syukri, Murniati AR, Yusrizal (Jurnal Administrasi Pendidikan : Program Pascasarjana Unsyiah, 2017)
Abstract: Leadership as a process to persuade people to be willing to do something voluntarily. This study aimed at describing the leadership program, leadership strategies, supporting factors and obstacles leadership of the head of Technology, Communication, and Education Agency’s Technical Implementing Unit (UPTD Tekkomdik) of Aceh Education Office in improving employees’ performance. The approach used in this study was a descriptive qualitative method. Data collection techniques used were interviews, observation, and documentation. The research subjects were head of UPTD Tekkomdik, Head of sub-Section, Head of Section, and employees of UPTD Tekkomdik. The results showed that: 1) Program to improve employees’ performance, including an increase in employees discipline, could encourage the employees to work with full responsibility and in accordance with the standard operational procedure (SOP) adopted; 2) The strategies used in improving the quality of service of the employees were situational leadership, for the employees who committed the work as usual, but they worked obediently in carrying out their duties, and a consultative and participatory leadership style. For the efforts to increase the commitment, the head often discussed with the employees to find a way approved by the employees; and 3) supporting factors in improving employee performance was conducive work, unambiguous the duties and functions of each employee, as well as a conducive relationship between subordinates and superiors. The obstacles that were still encountered were limited the ability of the head to conduct intensive monitoring of employees’ performance, there was still a small portion of employees who lack discipline in implementing their work and function, and a lack of work equipment causing hampered employee in performing the tasks that had been assigned by superiors.Keywords: leadership, capable of convincing, able to influence, motivation and employees’ performanceAbstrak: Kepemimpinan sebagai suatu proses untuk membujuk orang agar bersedia melakukan sesuatu secara sukarela. Penelitian ini bertujuan untuk mendeskripsikan tentang program kepemimpinan, strategi kepemimpinan, faktor pendukung dan penghambat kepemimpinan Kepala UPTD Balai Tekkomdik Dinas Pendidikan Aceh dalam meningkatkan kinerja pegawai. Pendekatan yang digunakan dalam penelitian ini deskriptif dengan metode kualitatif. Teknik pengumpulan data yang digunakan adalah wawancara, observasi, dan studi dokumentasi. Subjek  penelitian Kepala UPTD, Kepala Sub Bagian, Kepala Seksi, dan Pegawai UPTD Balai Tekkomdik Aceh. Hasil penelitian menunjukkan bahwa 1) Program dalam meningkatkan kinerja pegawai, di antaranya penerapan SOP, memberikan keteladanan, memberikan kesempatan untuk berdiskusi, peningkatan kedisiplinan pegawai, pegawai dapat bekerja dengan penuh tanggung jawab dan sesuai dengan SOP yang ditetapkan; 2) Strategi yang diterapkan dalam meningkatkan kinerja pegawai adalah dengan menerapkan kepemimpinan yang bersifat situasional bagi pegawai-pegawai yang komitmen kerjanya biasa, tetapi sikap mereka patuh dalam melaksanakan tugasnya, menerapkan gaya kepemimpinan konsultatif dan partisipatif. Sebagai upaya peningkatan komitmen kepala sering berdiskusi untuk mendapatkan cara yang disetujui oleh pegawai-pegawai; dan 3)Faktor pendukung dalam meningkatkan kinerja pegawai adalah terciptanya budaya  kerja yang kondusif, jelasnya tugas pokok dan fungsi masing-masing pegawai, serta terbina hubungan kondusif antara bawahan dengan atasan. Hambatan yang masih ditemui bahwa keterbatasan kemampuan pimpinan untuk melakukan pengawasan secara intensif terhadap kinerja pegawai, masih ada sebagian kecil pegawai yang kurang disiplin dalam melaksanakan tupoksinya, masih kurangnya perlengkapan kerja, sehingga menyebabkan terkendalanya pegawai dalam melaksanakan tugas yang telah diserahkan oleh atasan.Kata kunci: kepemimpinan, mampu meyakinkan, mampu mempengaruhi, motivasi dan Kinerja Pegawai